Two hours : the quest to run the impossible marathon - Caesar, Ed (Simon & Schuster, 2015)
"In this spellbinding book, journalist Ed Caesar takes us into the world of elite marathoners: some of the greatest runners on earth. Through the stories of these rich characters, like Kenyan Geoffrey Mutai, around whom the narrative is built, Caesar traces the history of the marathon as well as the science, physiology, and psychology involved in running so fast for so long. And he shows us why this most democratic of races retains its brutal, enthralling appeal--and why we are drawn to test ourselves to the limit,"--Amazon.com.